Respuesta :

Answer:

Hey there....

Step-by-step explanation:5

This is ur answer....

Expression : -x + 5

Working :-

x = Unknown number

x + 5 = Sum of the number and Five

x + 5 - 2x = Previous sum decreased by the the twice of the unknown number.

-x + 5 = combine the terms

Hope it helps!

Brainliest pls!

Have a good day!^^

Step-by-step explanation:

x is the number.

(x + 5) - 2x : the sum of the number and 5 decreased by twice the number.

or simplified without the brackets

x + 5 - 2x = 5 - x

it is not clear if you need the general expression showing both conditions (the first up there), or the then simplified result

5 - x